Blood Flow Regulates Glomerular Capillary Formation in Zebrafish Pronephros. Issue 4 (28th April 2022) - Nishimura, Yusuke; Ishii, Tomohiro; Ando, Koji; Yuge, Shinya; Nakajima, Hiroyuki; Zhou, Weibin; Mochizuki, Naoki; Fukuhara, Shigetomo
Key Points: During glomerular capillary formation, endothelial cells sprout from the dorsal aorta and surround the bilateral glomerular primordia. Blood flow maintains tubular structures of the capillaries surrounding the glomerular primordia. Blood flow also promotes glomerular incorporation of blood vessels by inducing glomerular remodeling. Visual Abstract: Abstract : Background: The renal glomerulus is a tuft of capillaries in Bowman's capsule and functions as a blood-filtration unit in the kidney. The unique glomerular capillary tuft structure is relatively conserved through vertebrate species. However, the morphogenetic mechanism governing glomerular capillary tuft formation remains elusive. Methods: To clarify how glomerular capillaries develop, we analyzed glomerular capillary formation in the zebrafish pronephros by exploiting fluorescence-based bio-imaging technology. Results: During glomerular capillary formation in the zebrafish pronephros, endothelial cells initially sprouted from the dorsal aorta and formed the capillaries surrounding the bilateral glomerular primordia in response to podocyte progenitor-derived vascular endothelial growth factor-A. After formation, blood flow immediately occurred in the glomerular primordia-associated capillaries, while in the absence of blood flow, they were transformed into sheet-like structures enveloping the glomerular primordia. Subsequently, blood flow induced formation of Bowman's space at the lateral sides of the bilateral glomerular primordia. Concomitantly, podocyte progenitors enveloped their surrounding capillaries while moving toward and coalescing at the midline. These capillaries then underwent extensive expansion and remodeling to establish a functional glomerular capillary tuft. However, stopping blood flow inhibited the remodeling of bilateral glomerular primordia, which therefore remained unvascularized but covered by the vascular sheets. Conclusions: We delineated the morphogenetic processes governing glomerular capillary tuft formation in the zebrafish pronephros and demonstrated crucial roles of blood flow in its formation. Blood flow maintains tubular structures of the capillaries surrounding the glomerular primordia and promotes glomerular incorporation of these vessels by inducing the remodeling of glomerular primordia.